A geomorphometric analysis in a mountain environment with the presence of a canyon: Case study of Boi River basin - González-Ávila, Itzayana; Paixão, Mauricio Andrades; Kobiyama, Masato (Revista Brasileira de Geomorfologia, 2022)
The river channels and the drainage network play an essential role in landscape evolution. Hydrogeomorphic studies provide valuable information to understand river basins and their processes by identifying relevant morphometric factors within river systems. In this sense, the aim of the present study was to carry out a geomorphometric analysis of the Boi River basin. Inside the basin having the Canyon Itaimbeizinho, there are three remarkable parts, Plateau, Hillslope, and Alluvial Plain. For the three parts, Area (A), Length of the Main River (L), Drainage Density (Dd), River Frequency (Rf), Sinuosity of the Main River (Si), Mean Topographic Index (TIm), and Lineament Density (Lm) were determined. Also, the Box-Counting method was performed to analyze the fractal dimension of the drainage network (DF) and river channels (df). Relations between these variables were verified through Pearson correlation analysis and the adjusted coefficient of determination. Parameters such as A, Si, and TIm are related to drainage network development (DF). While Dd, Dr, and Lm were associated with the development of river channels (df). The study allowed identifying geomorphological characteristics that provide relevant information for analyzing the Boi River basin parts. Geomorphometric studies can complement risk management and prevention studies, applied in the identification of areas with danger potential for the community.